Serum lactate is associated with increased illness severity in immunocompromised pediatric hematology oncology patients presenting to the emergency department with fever - Slatnick, Leonora Rose; Miller, Kristen; Scott, Halden F.; Loi, Michele; Esbenshade, Adam J.; Franklin, Anna; Lee-Sherick, Alisa B. (Frontiers in Oncology, 2022)
Introduction Determining which febrile pediatric hematology/oncology (PHO) patients will decompensate from severe infection is a significant challenge. Serum lactate is a well-established marker of illness severity in general adult and pediatric populations, however its utility in PHO patients is unclear given that chemotherapy, organ dysfunction, and cancer itself can alter lactate metabolism. In this retrospective analysis, we studied the association of initial serum lactate in febrile immunosuppressed PHO patients with illness severity, defined by the incidence of clinical deterioration events (CDE) and invasive bacterial infection (IBI) within 48 hours. Methods Receiver operating characteristic (ROC) curves were reported using initial lactate within two hours of arrival as the sole predictor for CDE and IBI within 48 hours. Using a generalized estimating equations (GEE) approach, the association of lactate with CDE and IBI within 48 hours was tested in univariate and multivariable analyses including covariates based on Quasi-likelihood under Independence Model Criterion (QIC). Additionally, the association of lactate with secondary outcomes (i.e., hospital length of stay (LOS), intensive care unit (PICU) admission, PICU LOS, non-invasive infection) was assessed. Results Among 897 encounters, 48 encounters had ≥1 CDE (5%), and 96 had ≥1 IBI (11%) within 48 hours. Elevated lactate was associated with increased CDE in univariate (OR 1.77, 95%CI: 1.48-2.12, p<0.001) and multivariable (OR 1.82, 95%CI: 1.43-2.32, p<0.001) analyses, longer hospitalization (OR 1.15, 95%CI: 1.07-1.24, p<0.001), increased PICU admission (OR 1.68, 95%CI: 1.41-2.0, p<0.001), and longer PICU LOS (OR 1.21, 95%CI: 1.04-1.4, p=0.01). Elevated lactate was associated with increased IBI in univariate (OR 1.40, 95%CI: 1.16-1.69, p<0.001) and multivariable (OR 1.49, 95%CI: 1.23-1.79, p<0.001) analyses. Lactate level was not significantly associated with increased odds of non-invasive infection (p=0.09). The QIC of the model was superior with lactate included for both CDE (305 vs. 325) and IBI (563 vs. 579). Conclusions These data demonstrated an independent association of elevated initial lactate level and increased illness severity in febrile PHO patients, suggesting that serum lactate could be incorporated into future risk stratification strategies for this population.